Research in organizational change and development. Volume 26 - Noumair, Debra A.; Shani, Abraham B. (Research in Organizational Change and Development,, 2018)
This volume providesnew conceptual insights, robust empirical studies, and thought-provoking chapters to help organizations improve health and wellbeing insociety. Some chapters dothis by addressing macro-level change: for example, consulting at the eco-system level anddiscussing the challenges entailed in developing intervention capabilities toimpact highly interdependent eco-systems; or discussing the learning and experience of a large system transformation projectconducted at a national level that had an impact on societal health andwellbeing. Other chapters extendtheory and integrate perspectives that heretofore have remained separate, suchas the 2017 Pasmore-Woodman Award winners, who provide an overview of theircollaborative attempts at intervening and making a difference in organization studies. The richness of the diverse collaborative contributions to thisvolume by leading scholars and scholar-practitioners from around the globeprovide an enriching and emerging body of knowledge.